N-[(1S,2S)-2-Amino-1,2-diphenylethyl]-4-methylbenzenesulfonamide [(S,S)-TsDPEN] - Schlemmer, Claudine (International Union of Crystallography, 2010)
The crystal structure of the title compound, C(21)H(22)N(2)O(2)S, shows a network of N—H⋯N and N—H⋯O hydrogen bonds. The tolyl and 1-phenyl rings are almost mutually coplanar [7.89 (9)°], while the 2-phenyl ring makes a dihedral angle of 50.8 (1) ° with the 1-phenyl ring. An intramolecular N—H⋯N hydrogen bond stabilizes the molecular conformation.